Effects of resistance training, tai chi chuan and mat pilates on multiple health variables in postmenopausal women - Araújo-Gomes, Rafaela Cristina; Valente-Santos, Marcia; Vale, Rodrigo Gomes De Souza; Drigo, Alexandre Janotta [UNESP]; Borba-Pinheiro, Claudio Joaquim (Asociacion Espanola de Analisis del Rendimiento Deportivo, 2019)
Objective: To compare the effect of two concurrent training methods on the muscle strength, functional autonomy, cardiorespiratory capacity and quality of life (QoL) of postmenopausal women. Material and methods: Thirty-eight volunteers were allocated to two groups: Resistance Training (RT)+Tai Chi Chuan (TC) (n=16), and RT+Mat Pilates (MP) (n=12). For the RT+TC group, RT was linearly periodized twice a week, alternating weekly with TC. In the RT+MP group, RT was non-linearly periodized and alternated with MP in five sessions a week over a period of 16 weeks. Results: Intragroup improvement in QoL was observed for the physical health of RT+MP. The Cooper test showed improvement in the prediction test for both groups. Functional autonomy improved in the following: rising from a ventral decubitus position, rising from a sitting position, walking 10 meters, putting on and taking off a t-shirt (PTTs) and the GDLAM index (GI) in the RT+MP group. For RT+TC, PTTs and GI improved. With respect to strength, there was intragroup improvement in the RT+MP group for all upper limb exercises, knee flexion and 45° leg press. On the other hand, the RT+TC group showed improvements in high shoulder adduction, elbow extension, low shoulder adduction, pec deck pectorals and 45° leg press. Intergroup analysis showed better results in the 10mW test for RT+MP. Conclusion: Both methods showed significant improvements in functional autonomy and muscle strength, as well as maintenance of QoL and cardiorespiratory capacity. Intergroup analysis indicated better results with the RT+MP program.
Keywords: Functional autonomy; Health; Physical exercise; Postmenopausal; Women